Corpus callosal atrophy and associations with cognitive impairment in Parkinson disease. (28th March 2017) - Goldman, Jennifer G.; Bledsoe, Ian O.; Merkitch, Doug; Dinh, Vy; Bernard, Bryan; Stebbins, Glenn T.
Abstract : Objective: To investigate atrophy of the corpus callosum on MRI in Parkinson disease (PD) and its relationship to cognitive impairment. Methods: One hundred patients with PD and 24 healthy control participants underwent clinical and neuropsychological evaluations and structural MRI brain scans. Participants with PD were classified as cognitively normal (PD-NC; n = 28), having mild cognitive impairment (PD-MCI; n = 47), or having dementia (PDD; n = 25) by Movement Disorder Society criteria. Cognitive domain (attention/working memory, executive function, memory, language, visuospatial function) z scores were calculated. With the use of FreeSurfer image processing, volumes for total corpus callosum and its subsections (anterior, midanterior, central, midposterior, posterior) were computed and normalized by total intracranial volume. Callosal volumes were compared between participants with PD and controls and among PD cognitive groups, covarying for age, sex, and PD duration and with multiple comparison corrections. Regression analyses were performed to evaluate relationships between callosal volumes and performance in cognitive domains. Results: Participants with PD had reduced corpus callosum volumes in midanterior and central regions compared to healthy controls. Participants with PDD demonstrated decreased callosal volumes involving multiple subsections spanning anterior to posterior compared to participants with PD-MCI and PD-NC. Regional callosal atrophy predicted cognitive domain performance such that central volumes were associated with the attention/working memory domain; midposterior volumes with executive function, language, and memory domains; and posterior volumes with memory and visuospatial domains. Conclusions: Notable volume loss occurs in the corpus callosum in PD, with specific neuroanatomic distributions in PDD and relationships of regional atrophy to different cognitive domains. Callosal volume loss may contribute to clinical manifestations of PD cognitive impairment.